Magnetic resonance imaging abnormalities in idiopathic intracranial hypertension: a study of 40 female patients - Storarri, Ana Carolina Montouro; Lee, Annelise Akemi Higa; Gonzaga, Bruno Pissolati Mattos; Arthuzo , Lorrane Campidelli; Sawada, Luis Armando; Santos, Beatriz Marques dos; Marques , Thassia Cavalcante de Oliveira Moraes; Domingues, Renan Barros (Headache Medicine, 2024)
Introduction Idiopathic intracranial hypertension (IIH) is a condition characterized by increased intracranial pressure with no detectable cause. MRI is an importat tool in diagnosing and understanding IIH, providing insights into the anatomical changes associated with this condition. This study aims to describe the MRI findings in a cohort of 40 female patients diagnosed with IIH. Objective To evaluate the frequency and type of abnormalities detected on MRI in female patients with IIH. Methods We conducted a retrospective analysis of MRI findings in 40 female patients diagnosed with IIH. The average age of the patients was 33.9 years (standard deviation of 11.5 years). The MRI abnormalities evaluated included sella turcica deformities, optic nerve abnormalities (including optic nerve tortuosity, distended optic nerve sheath, and optic nerve head protrusion), globe flattening, and transverse sinus stenosis. The data were analyzed to determine the prevalence of each abnormality. All the patients were evaluated at the Headache Outpatient Clinic of Santa Casa de Misericórdia de São Paulo. Results The analysis revealed the following abnormalities: Sella turcica deformities in 14 patients (35%) Optic nerve abnormalities in 35 patients (87.5%) Globe flattening in 8 patients (20%) Transverse sinus stenosis in 14 patients (35%) Conclusion Our study demonstrates that optic nerve abnormalities are the most frequent MRI finding in female patients with IIH, observed in 87.5% of cases. This is a higher frequency compared to sella turcica deformities, which were present in 35% of the patients. These findings differ from other series in the literature, where sella turcica abnormalities are often reported as more common. This highlights the variability in anatomical manifestations of IIH and underscores the importance of comprehensive MRI evaluation in these patients.